Effects of ApoE genotype on clinical phenotypes in early‐onset and late‐onset Alzheimer's disease in China: Data from the PUMCH dementia cohort. Issue 11 (23rd September 2021) - Dong, Liling; Li, Jie; Liu, Caiyan; Mao, Chenhui; Wang, Jie; Lei, Dan; Huang, Xinying; Chu, Shanshan; Hou, Bo; Feng, Feng; Sha, Longze; Xu, Qi; et al.
Abstract: Introduction: To investigate the heterogeneous effect of Apolipoprotein E (ApoE) genotype on clinical phenotypes in early‐onset Alzheimer's disease (EOAD) and late‐onset Alzheimer's disease (LOAD), respectively. Methods: 785 probable AD patients were enrolled from the dementia cohort of Peking Union Medical College Hospital (PUMCH), China. There were 386 EOAD and 399 LOAD cases. All individuals finished history inquiry, neurological examination, blood biochemical test, neuropsychological screening test, electroencephalography, brain CT/MRI, and ApoE genotyping. Some participants had neuropsychological domain assessment ( n = 317), MRI morphometry ( n = 130), CSF testing of Aβ42, p‐tau, t‐tau ( n = 144), or DNA sequencing ( n = 690). The variables were compared mainly between ɛ4 carriers and non‐carriers in EOAD and LOAD, respectively. Results: In LOAD, ɛ4 carriers showed female predominance; worse performance in trail making test, delayed recall of auditory verbal learning test (AVLT) and rey complex figure; smaller hippocampal, parahippocampal, and entorhinal volume, as compared to ɛ4 non‐carriers. In EOAD, ɛ4 carriers had lower scores in AVLT, episodic memory and modified Luria's tapping task; but less cortical atrophy in entorhinal, middle cingulate, inferior frontal, and parieto‐occipital regions, in comparison to ɛ4 non‐carriers. 6.2% (43/690) subjects harbored potential causative mutations in APP, PSEN1, and PSEN2. In both EOAD and LOAD, no differences were observed between ɛ4 carriers and non‐carriers in CSF levels of Aβ42, p‐tau, t‐tau, or mutation frequency. Conclusions: ApoE exerts a heterogeneous effect on clinical phenotypes in EOAD and LOAD, which might be related to the different genetic and pathological basis underlying them. Abstract : ApoE exerts a heterogeneous effect on clinical phenotype in EOAD and LOAD. In LOAD, ApoE‐ɛ4 genotype is associated with severe medial temporal atrophy and a higher p‐tau level. However, in EOAD, ɛ4 genotype is associated with less cortical atrophy in widespread areas, and lower t‐tau level.